PRODUKSI BIOGAS DARI ECENG GONDOK (EICCHORNIA CRASSIPES) : KAJIAN KONSISTENSI DAN pH TERHADAP BIOGAS DIHASILKAN - Arnold Yonathan; Avianda Rusba Prasetya; Bambang Pramudono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Water hyacinth (Eicchornia crassipes) is one of the weeds type which has the fastest growth amongothers, but it can be used in the biogas production because it contains large number ofhemiselulosa. Anaerobic digestion is a process where the microorganism is doing a biodegradablematerial split within the oxygen devoid. The biogas making process begins at cutting up the waterhyacinth, to be added with the water and to be blended with cow dung later. When the mixedsolution is already well-suited with the operation variable, pour it into the pre-treatmentbiodigester by adding the H2SO4 into the (substrat). The process will present the result atcomposition variable, which is showing the largest biogas production at 2:2,5 composition in1.162,97mL, and the smallest biogas production at 2:1 composition in 12,85mL. The bestcomposition from the fermentation process has done before is used as the dependent variable witha pH variable change. The result shows at the pH interval 4 -7, the biogas production isincreasing, and will decrease at the pH 8. The largest biogas production is at the variable pH 7 inthe amount of 1.162,97mL. The GC analysis result shows the metana that contains inside thebiogas is 0,03mol/100gr water hyacinth.